Optimalisasi Fungsi Lembaga Pemasyarakatan Perempuan Kelas II A Dalam Kaitannya Dengan Sistim Peradilan Pidana - Yonani, Yonani (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
The rule of law is a state that takes the law first and guarantees the security of its citizens. The sustainability of ethnic, national and social life in Indonesia requires the implementation of the practice of the rule of law. The term Indonesian rule of law is often associated with the rechtsstaat and rule-of-law, based on the number of constitutions that have ever been made in Indonesia. These constitutions all affirm that Indonesia is a rule of law. Human rights must be taken into account when assisting prisoners. If rights are seen as a form of compensation that represents pain, then the only reason for suffering is for the prisoner to lose his freedom, both temporarily and for the rest of his life.